Adhesive film as well as composition and method for reducing relative displacement of adhesive film and glass in humid environment
By adding silane and silane hydrolysis catalyst to the POE film of the photovoltaic module, the presence of water molecules promotes silane hydrolysis and forms chemical bonds with glass, solving the problem of relative slippage with glass in a humid environment, and significantly improving the adhesion and service life.
Patent Information
- Application Number
- CN202311212327.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
AI Technical Summary
The POE film of existing photovoltaic modules is prone to relatively slipping with the glass in humid environments, resulting in a reduced service life.
By adding silane and silane hydrolysis catalyst to the adhesive film, the presence of water molecules promotes silane hydrolysis and forms chemical bonds with the glass surface, thereby enhancing the adhesion between the adhesive film and glass and preventing slippage.
In humid environments, the silane hydrolysis catalyst accelerates the hydrolysis of silane, forms chemical bonds to bond with glass, significantly reducing the relative slippage between the adhesive film and glass, and extending service life.
Smart Images

Figure BDA0004457864740000091 
Figure BDA0004457864740000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of photovoltaic adhesive films, and more specifically, to an adhesive film, a composition and a method for reducing relative displacement between the adhesive film and glass in a humid environment. Background Art
[0002] Currently, the commonly used films for photovoltaic modules mainly include EVA films and POE films. Although EVA films account for a large proportion, the high water permeability of EVA films will affect their service life. Therefore, the use of POE films has increased significantly in recent years due to their low water vapor permeability. However, the POE molecular formula has non-polar characteristics, and some of the functional additives added are polar substances. Due to poor compatibility, POE films have relative slip.
[0003] In the prior art, in order to prevent the POE film from slipping, UV curing, electron beam irradiation and other methods are mainly used to pre-crosslink the additives with the resin to lock the additives and reduce the effect of the additives on slippage. However, this will increase the process cost and the additives cannot fully react. Alternatively, the amount of additives added is reduced or no additives are added. However, this will also lead to a decrease in the overall performance of the film, such as softness and bonding effect. Although the above methods can improve the slippage of the film caused by the additives, they cannot improve the phenomenon that in a humid environment, polar water molecules adhere to the glass surface, causing the relative slippage between the film and the glass to increase. Summary of the invention
[0004] In order to prevent the adhesive film from relatively slipping in a humid environment, the present application provides an adhesive film, a composition and a method for reducing the relative displacement between the adhesive film and glass in a humid environment.
[0005] In a first aspect, the present application provides a composition for reducing relative displacement between an adhesive film and glass in a humid environment, comprising silane contained in the adhesive film and a silane hydrolysis catalyst, wherein the silane hydrolysis catalyst promotes the hydrolysis of the silane, thereby bonding the adhesive film to the glass.
[0006] By adopting the above technical solution, in a humid environment, the presence of water molecules can promote the hydrolysis of silane, and the silane hydrolysis catalyst accelerates the hydrolysis of silane, so that the silane and the hydroxyl groups on the glass surface undergo a dehydration reaction and form a chemical bond, so that the adhesive film and the glass are bonded, and thus the adhesive film is not easy to cause relative slip between the adhesive film and the glass due to polar water adhering to the non-polar glass surface in a humid environment; as the water molecules further diffuse, they enter the interior of the silane and even the interior of the adhesive film, and under the synergistic action of the silane hydrolysis catalyst, the silane is hydrolyzed and condensed, thereby forming an intermolecular Si-O-Si bond, so that the interior of the silane or the adhesive film is slowly pre-crosslinked to form a dense molecular structure to protect the battery cell from damage by water molecules.
[0007] Optionally, the silane hydrolysis catalyst is an organic tin catalyst having the general formula R n S n X4, wherein: n is an integer of 1-4, R is a linear or branched C1-C30 alkyl group, a C5-C14 cycloalkyl group or a C6-C16 aryl group, and X is a substituent selected from one of halogen, hydroxyl, carboxyl, amino, ester, thiol alkyl, anhydride, isocyanate, mercapto, sulfonic acid, epoxy or cyano groups.
[0008] Optionally, the organotin catalyst is selected from one or more of dibutyltin dilaurate, dibutyltin dineodecanoate, dibutyltin dithioacetate, dibutyltin didodecylsulfide, dibutyltin dioleate, dibutyltin diacetate, stannous octoate, dialkyltin dimaleate, and alkyltin dithiolate.
[0009] By adopting the above technical solution, in an environment with a humidity greater than 70%, the organic tin catalyst can accelerate the hydrolysis of silane, and then form chemical bonds with the hydroxyl groups on the glass surface, thereby increasing the interfacial adhesion between the film and the glass, and preventing the non-polar film and the glass from relative slipping. At the same time, after the silane is hydrolyzed, Si-O-Si bonds are formed between molecules, and internal cross-linking is performed to form a dense structure to prevent moisture penetration.
[0010] Optionally, the silane is selected from one or more of vinyltrimethoxysilane, vinyltriethoxysilane, tetramethyltetravinylcyclotetrasiloxane, aminopropyltriethoxysilane, aminopropyltrimethoxysilane, vinyltriacetoxysilane, isobutyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and vinyltriethoxy oligomer.
[0011] By adopting the above technical solution, the silicon in the above silane is connected with a hydroxyl group. In a humid environment, silane is easily hydrolyzed. Under the action of the silane hydrolysis catalyst, the hydrolysis is accelerated, thereby producing a dehydration reaction with the hydroxyl group on the glass surface, forming a chemical bond with the glass surface, increasing the adhesion between the film and the glass, and reducing the relative slippage of the film to the glass package. Moreover, under the action of the silane hydrolysis catalyst, the silane is hydrolyzed to form an intermolecular silicon-oxygen bond, so that the silane is slowly pre-crosslinked to form a dense molecular structure to prevent further penetration of moisture.
[0012] Preferably, the mass ratio of the silane to the silane hydrolysis catalyst is 1:0.001-0.01, the silane is vinyltriethoxysilane, and the silane hydrolysis catalyst is dibutyltin dilaurate.
[0013] By adopting the above technical scheme, vinyl triethoxysilane and dibutyl tin dilaurate in the above mass ratio are used as silane and silane hydrolysis catalyst respectively. In a humid environment, the silane hydrolysis catalyst promotes the hydrolysis of silane, which then undergoes a dehydration reaction with the hydroxyl groups on the glass surface to form a chemical bond connection, thereby increasing the bonding strength between the film and the glass and reducing the relative slip between the film and the glass.
[0014] Preferably, the mass ratio of the silane to the silane hydrolysis catalyst is 1:0.001-0.01, the silane is vinyltrimethoxysilane, and the silane hydrolysis catalyst is di(dodecylsulfide)dibutyltin.
[0015] By adopting the above technical scheme, vinyltrimethoxysilane and dibutyltin(dodecylsulfide) in the above mass ratio are used as silane and silane hydrolysis catalyst respectively. In a humid environment, the silane hydrolysis catalyst promotes the hydrolysis of silane, and the hydroxyl groups on the surface of the adhesive film and the glass undergo a dehydration reaction to form a chemical bond connection, thereby increasing the bonding strength between the adhesive film and the glass and reducing the relative slip between the adhesive film and the glass.
[0016] In a second aspect, the present application provides an adhesive film, which adopts the following technical solution: A glue film comprises a polyolefin matrix resin, a crosslinking agent, a co-crosslinking agent, a silane hydrolysis catalyst and silane, wherein the polyolefin matrix resin contains 0.1-2 parts by weight of silane and 0.001-0.1 parts by weight of the silane hydrolysis catalyst relative to 100 parts by weight of the polyolefin matrix resin, so that the silane hydrolysis catalyst promotes the hydrolysis reaction of the silane, thereby bonding the glue film to the glass.
[0017] Since the polyolefin matrix resin is a non-polar substance, small molecules (such as silane) migrate to the surface of the film to form a thin layer similar to an "oil film", causing the film to produce relative slip. Moreover, in an environment with a humidity greater than 70%, water molecules in the environment adhere to the surface of the glass. The film with a thin layer similar to an "oil film" on the surface is laid on the wet glass, which will aggravate the relative slip between the film and the glass. Therefore, in the present application, silane and a silane hydrolysis catalyst are added to the polyolefin matrix resin. Due to the presence of water molecules in a humid environment, the hydrolysis of silane is promoted. The silane hydrolysis catalyst accelerates the hydrolysis of silane, undergoes a dehydration reaction with the hydroxyl groups on the glass surface, and forms a chemical bond, thereby enhancing the bonding force between the interface and the glass, thereby preventing the film with a thin layer similar to an "oil film" on the surface from being laid on the wet glass in a humid environment, causing the film and the glass to produce relative slip. Inside the silane, or even inside the film, the silane is hydrolyzed under the synergistic action of the silane hydrolysis catalyst to form Si-O-Si bonds between molecules, thereby slowly pre-crosslinking the inside of the silane or the film to form a dense molecular structure, preventing further diffusion of water molecules to protect the battery cell from damage caused by water molecules.
[0018] Preferably, relative to 100 parts by weight of the polyolefin base resin, it contains 0.5-1 parts by weight of silane and 0.002-0.01 parts by weight of Silane hydrolysis catalyst.
[0019] By adopting the above technical solution, the dosage of silane and silane silicone catalyst in the adhesive film is more precise, so that the anti-slip effect of the prepared adhesive film in a humid environment is better.
[0020] Preferably, the silane hydrolysis catalyst is an organotin catalyst having the general formula R n S n X4, wherein: n is an integer of 1-4, R is a linear or branched C1-C30 alkyl group, a C5-C14 cycloalkyl group or a C6-C16 aryl group, and X is a substituent selected from one of halogen, hydroxyl, carboxyl, amino, ester, thiol alkyl, anhydride, isocyanate, mercapto, sulfonic acid, epoxy or cyano groups.
[0021] Preferably, the organotin catalyst is selected from one or more of dibutyltin dilaurate, dibutyltin dineodecanoate, dioctyltin dioctanoate, isooctyl dibutyltin dithioacetate, dibutyltin didodecylsulfide, dibutyltin dioleate, dibutyltin diacetate, stannous octoate, dialkyltin dimaleate, and alkyltin dithiolate.
[0022] Preferably, the silane is selected from one or more of vinyltrimethoxysilane, vinyltriethoxysilane, tetramethyltetravinylcyclotetrasiloxane, aminopropyltriethoxysilane, aminopropyltrimethoxysilane, vinyltriacetoxysilane, isobutyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and vinyltriethoxy oligomer.
[0023] Preferably, the mass ratio of the silane to the silane hydrolysis catalyst is 1:0.001-0.01, the silane is vinyltriethoxysilane, and the silane hydrolysis catalyst is dibutyltin dilaurate.
[0024] Preferably, the mass ratio of the silane to the silane hydrolysis catalyst is 1:0.001-0.01, the silane is vinyltrimethoxysilane, and the silane hydrolysis catalyst is di(dodecylsulfide)dibutyltin.
[0025] Preferably, the polyolefin base resin is an ethylene-α-olefin copolymer.
[0026] By adopting the above technical scheme, ethylene-α-olefin copolymer is prepared by polymerization of ethylene and α-olefin copolymer with carbon number of 3-20, and is used for photovoltaic modules. It has strong stability and long service life, improves the efficiency of modules, and has high transparency and good durability.
[0027] Preferably, the ethylene-α-olefin copolymer is selected from the group consisting of ethylene-1-butene copolymer, ethylene-1-hexene copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-1-octene copolymer, ethylene-1-butene-1-hexene copolymer, ethylene-1-butene-4-methyl-1-pentene copolymer, ethylene-1-butene-1-octene copolymer and ethylene-1-hexene-1-octene copolymer.
[0028] Preferably, the density of the ethylene-α-olefin copolymer is 0.85-0.88 g / cm 3 .
[0029] By adopting the above technical solution, the ethylene-α-olefin copolymer with the above density can improve the mechanical strength of the film after molding.
[0030] Preferably, the cross-linking agent is selected from one or more of benzoyl peroxide, tert-amyl peroxy 2-ethylhexyl carbonate, di(tert-butylperoxy)diisopropylbenzene, tert-butyl peroxybenzoate, tert-butyl peroxy 2-ethylhexyl carbonate, n-butyl-4,4-di-tert-butyl peroxyvalerate, 1,1-di-tert-butyl peroxy-3,3,5-trimethylcycloethane and 1,1-di-tert-butyl peroxy-3,3,5-trimethylcycloethane.
[0031] In a third aspect, the present application provides a method for reducing the relative displacement between the adhesive film and the glass in a humid environment, using the following technical solution: A method for reducing relative displacement between an adhesive film and glass in a humid environment comprises the following steps: (a) preparing a film, wherein the surface of the film contains silane and a silane hydrolysis catalyst; (b) Laying the adhesive film on the glass; (c) the silane hydrolysis catalyst promotes the hydrolysis of the silane, undergoes a dehydration reaction with the glass, and forms a chemical bond; (d) The adhesive film is bonded to the glass.
[0032] In summary, this application has the following beneficial effects: 1. Since the present application uses a polyolefin matrix resin, silane, a silane hydrolysis catalyst, etc. to prepare the adhesive film, in a humid environment, the presence of water molecules promotes the hydrolysis of silane. Under the action of the silane hydrolysis catalyst, the silane accelerates the hydrolysis, undergoes a dehydration reaction with the glass, and forms a chemical bond with the glass surface, thereby increasing the bonding strength between the adhesive film and the glass and reducing the relative slip between the adhesive film and the glass.
[0033] 2. In the present application, vinyl triethoxysilane is preferably used as silane and dibutyl tin dilaurate is used as an organic tin catalyst. The two are added to the adhesive film in a certain proportion. In the presence of water molecules and under the catalytic action of dibutyl tin dilaurate, vinyl triethoxysilane accelerates hydrolysis and then undergoes a dehydration reaction with the hydroxyl groups on the glass surface to form a chemical bond connection, thereby improving the adhesion between the adhesive film and the glass and enhancing the anti-slip effect of the adhesive film in a humid environment.
[0034] 3. In the present application, vinyltrimethoxysilane is preferably used as the silane, and dibutyltin(dodecylsulfide) is used as the silane hydrolysis catalyst, and is added to the film in a certain proportion. In a humid environment, dibutyltin(dodecylsulfide) accelerates the hydrolysis of vinyltrimethoxysilane, thereby causing a dehydration reaction between the silane and the glass surface, increasing the bonding strength between the film and the glass, and improving the anti-slip effect of the film. DETAILED DESCRIPTION Example
[0035] Example 1: A film comprising the following raw materials in parts by weight (kg): 100 parts of a polyolefin matrix resin, 6 parts of a crosslinking agent, 1 part of a silane, 0.01 parts of a silane hydrolysis catalyst, 0.2 parts of a co-crosslinking agent, and 0.1 parts of an anti-aging agent, wherein the polyolefin matrix resin is an ethylene-1-butene copolymer formed by polymerization of ethylene and 1-butene, and has a density of 0.877 g / cm 3 The model is LG Chemical LF675 from South Korea, the cross-linking agent is tert-butyl peroxy 2-ethylhexyl carbonate, the auxiliary cross-linking agent is trimethylolpropane trimethacrylate, the antioxidant is benzoic acid (2,2,6,6-tetramethyl-4-hydroxypiperidinyl) ester, the silane is vinyltriethoxysilane, and the silane hydrolysis catalyst is an organic tin catalyst, specifically dibutyltin dilaurate; wherein the silane and the silane hydrolysis catalyst constitute a composition that reduces the relative displacement between the adhesive film and the glass in a humid environment, and the silane hydrolysis catalyst promotes the hydrolysis of silane, thereby improving the bonding between the adhesive film and the glass.
[0036] The method for preparing the above-mentioned adhesive film comprises the following steps: According to the above dosage, the polyolefin matrix resin, crosslinking agent, silane, silane hydrolysis catalyst, co-crosslinking agent and anti-aging agent are mixed evenly, the evenly mixed material is added to the melt extrusion casting machine for extrusion, the temperature is controlled at 90°C, the extrudate is cast, cooled and embossed to obtain a film with a thickness of 0.45m.
[0037] A method for reducing relative displacement between an adhesive film and glass in a humid environment comprises the following steps: (a) preparing the above-mentioned film, wherein the surface of the film contains silane and a silane hydrolysis catalyst; (b) Laying the adhesive film on the glass; (c) a silane hydrolysis catalyst promotes the hydrolysis of the silane, and performs a dehydration reaction with the glass to form a chemical bond; (d) Adhesive film is bonded to glass.
[0038] Example 2: A film comprising the following raw materials in parts by weight (kg): 100 parts of a polyolefin matrix resin, 6 parts of a crosslinking agent, 1 part of a silane, 0.001 parts of a silane hydrolysis catalyst, 0.2 parts of a co-crosslinking agent, and 0.1 parts of an anti-aging agent, wherein the polyolefin matrix resin is an ethylene-1-butene copolymer formed by polymerization of ethylene and 1-butene, and has a density of 0.877 g / cm 3 The model is LG Chemical LF675 from South Korea, the cross-linking agent is tert-butyl peroxy 2-ethylhexyl carbonate, the auxiliary cross-linking agent is trimethylolpropane trimethacrylate, the antioxidant is benzoic acid (2,2,6,6-tetramethyl-4-hydroxypiperidinyl) ester, the silane is vinyltriethoxysilane, and the silane hydrolysis catalyst is an organic tin catalyst, specifically dibutyltin dilaurate.
[0039] The method for preparing the above-mentioned adhesive film comprises the following steps: According to the above dosage, the polyolefin matrix resin, crosslinking agent, silane, silane hydrolysis catalyst, co-crosslinking agent and anti-aging agent are mixed evenly, the evenly mixed material is added to the melt extrusion casting machine for extrusion, the temperature is controlled at 90°C, the extrudate is cast, cooled and embossed to obtain a film with a thickness of 0.45m.
[0040] Example 3: A film comprising the following raw materials in parts by weight (kg): 100 parts of a polyolefin matrix resin, 6 parts of a crosslinking agent, 1 part of a silane, 0.01 parts of a silane hydrolysis catalyst, 0.2 parts of a co-crosslinking agent, and 0.1 parts of an anti-aging agent, wherein the polyolefin matrix resin is an ethylene-1-butene copolymer formed by polymerization of ethylene and 1-butene, and has a density of 0.877 g / cm 3The model is LG Chemical LF675 from South Korea, the cross-linking agent is tert-butyl peroxy 2-ethylhexyl carbonate, the auxiliary cross-linking agent is trimethylolpropane trimethacrylate, the antioxidant is benzoic acid (2,2,6,6-tetramethyl-4-hydroxypiperidinyl) ester, the silane is vinyltriethoxysilane, and the silane hydrolysis catalyst is an organic tin catalyst, specifically di(dodecylsulfide) dibutyltin.
[0041] The method for preparing the above-mentioned adhesive film comprises the following steps: According to the above dosage, the polyolefin matrix resin, crosslinking agent, silane, silane hydrolysis catalyst, co-crosslinking agent and anti-aging agent are mixed evenly, the evenly mixed material is added to the melt extrusion casting machine for extrusion, the temperature is controlled at 90°C, the extrudate is cast, cooled and embossed to obtain a film with a thickness of 0.45m.
[0042] Example 4: A film comprising the following raw materials in parts by weight (kg): 100 parts of a polyolefin matrix resin, 6 parts of a crosslinking agent, 1 part of a silane, 0.01 parts of a silane hydrolysis catalyst, 0.2 parts of a co-crosslinking agent, and 0.1 parts of an anti-aging agent, wherein the polyolefin matrix resin is an ethylene-1-butene copolymer formed by polymerization of ethylene and 1-butene, and has a density of 0.877 g / cm 3 The model is South Korean LG Chemical LF675, the cross-linking agent is tert-butyl peroxy 2-ethylhexyl carbonate, the auxiliary cross-linking agent is trimethylolpropane trimethacrylate, the antioxidant is benzoic acid (2,2,6,6-tetramethyl-4-hydroxypiperidinyl) ester, the silane is vinyltrimethoxysilane, and the silane hydrolysis catalyst is an organic tin catalyst, specifically dibutyltin dilaurate.
[0043] The method for preparing the above-mentioned adhesive film comprises the following steps: According to the above dosage, the polyolefin matrix resin, crosslinking agent, silane, silane hydrolysis catalyst, co-crosslinking agent and anti-aging agent are mixed evenly, the evenly mixed material is added to the melt extrusion casting machine for extrusion, the temperature is controlled at 90°C, the extrudate is cast, cooled and embossed to obtain a film with a thickness of 0.45m.
[0044] Example 5: A film comprising the following raw materials in parts by weight (kg): 100 parts of a polyolefin matrix resin, 6 parts of a crosslinking agent, 1 part of a silane, 0.01 parts of a silane hydrolysis catalyst, 0.2 parts of a co-crosslinking agent, and 0.1 parts of an anti-aging agent, wherein the polyolefin matrix resin is an ethylene-1-butene copolymer formed by polymerization of ethylene and 1-butene, and has a density of 0.877 g / cm 3The model is LG Chemical LF675 from South Korea, the cross-linking agent is tert-butyl peroxy 2-ethylhexyl carbonate, the auxiliary cross-linking agent is trimethylolpropane trimethacrylate, the antioxidant is benzoic acid (2,2,6,6-tetramethyl-4-hydroxypiperidinyl) ester, the silane is vinyl triethoxy oligomer, and the silane hydrolysis catalyst is an organic tin catalyst, specifically dibutyltin dilaurate.
[0045] The method for preparing the above-mentioned adhesive film comprises the following steps: According to the above dosage, the polyolefin matrix resin, crosslinking agent, silane, silane hydrolysis catalyst, co-crosslinking agent and anti-aging agent are mixed evenly, the evenly mixed material is added to the melt extrusion casting machine for extrusion, the temperature is controlled at 90°C, the extrudate is cast, cooled and embossed to obtain a film with a thickness of 0.45m.
[0046] Example 6: A film comprising the following raw materials in parts by weight (kg): 100 parts of a polyolefin matrix resin, 6 parts of a crosslinking agent, 1 part of a silane, 0.01 parts of a silane hydrolysis catalyst, 0.2 parts of a co-crosslinking agent, and 0.1 parts of an anti-aging agent, wherein the polyolefin matrix resin is an ethylene-1-butene copolymer formed by polymerization of ethylene and 1-butene, and has a density of 0.877 g / cm 3 The model is LG Chemical LF675 from South Korea, the cross-linking agent is tert-butyl peroxy 2-ethylhexyl carbonate, the auxiliary cross-linking agent is trimethylolpropane trimethacrylate, the antioxidant is benzoic acid (2,2,6,6-tetramethyl-4-hydroxypiperidinyl) ester, the silane is vinyl triethoxy oligomer, and the silane hydrolysis catalyst is an organic tin catalyst, specifically di(dodecylsulfide) dibutyltin.
[0047] The method for preparing the above-mentioned adhesive film comprises the following steps: According to the above dosage, the polyolefin matrix resin, crosslinking agent, silane, silane hydrolysis catalyst, co-crosslinking agent and anti-aging agent are mixed evenly, the evenly mixed material is added to the melt extrusion casting machine for extrusion, the temperature is controlled at 90°C, the extrudate is cast, cooled and embossed to obtain a film with a thickness of 0.45m.
[0048] Example 7: A film comprising the following raw materials in parts by weight (kg): A film comprising the following raw materials in parts by weight: 100 parts of a polyolefin matrix resin, 6 parts of a crosslinking agent, 1 part of a silane, 0.01 parts of a silane hydrolysis catalyst, 0.2 parts of a co-crosslinking agent and 0.1 parts of an anti-aging agent, wherein the polyolefin matrix resin is an ethylene-1-butene copolymer formed by polymerization of ethylene and 1-butene, and has a density of 0.877 g / cm 3The model is LG Chemical LF675 from South Korea, the cross-linking agent is tert-butyl peroxy 2-ethylhexyl carbonate, the auxiliary cross-linking agent is trimethylolpropane trimethacrylate, the antioxidant is benzoic acid (2,2,6,6-tetramethyl-4-hydroxypiperidinyl) ester, the silane is vinyltriethoxysilane, and the silane hydrolysis catalyst is an organic tin catalyst, specifically dibutyltin dithioacetate isooctyl ester.
[0049] The method for preparing the above-mentioned adhesive film comprises the following steps: According to the above dosage, the polyolefin matrix resin, crosslinking agent, silane, silane hydrolysis catalyst, co-crosslinking agent and anti-aging agent are mixed evenly, the evenly mixed material is added to the melt extrusion casting machine for extrusion, the temperature is controlled at 90°C, the extrudate is cast, cooled and embossed to obtain a film with a thickness of 0.45m.
[0050] Example 8: A film comprising the following raw materials in parts by weight (kg): A film comprising the following raw materials in parts by weight: 100 parts of a polyolefin matrix resin, 3 parts of a crosslinking agent, 1.5 parts of a silane, 0.002 parts of a silane hydrolysis catalyst, 0.3 parts of a co-crosslinking agent, and 0.2 parts of an anti-aging agent, wherein the polyolefin matrix resin is an ethylene-1-butene copolymer formed by polymerization of ethylene and 1-butene, and has a density of 0.877 g / cm 3 The model is LG Chemical LF675 from South Korea, the cross-linking agent is tert-butyl peroxy 2-ethylhexyl carbonate, the auxiliary cross-linking agent is trimethylolpropane trimethacrylate, the antioxidant is benzoic acid (2,2,6,6-tetramethyl-4-hydroxypiperidinyl) ester, the silane is vinyltriethoxysilane, and the silane hydrolysis catalyst is an organic tin catalyst, specifically dibutyltin dilaurate.
[0051] The method for preparing the above-mentioned adhesive film comprises the following steps: According to the above dosage, the polyolefin matrix resin, crosslinking agent, silane, silane hydrolysis catalyst, co-crosslinking agent and anti-aging agent are mixed evenly, the evenly mixed material is added to the melt extrusion casting machine for extrusion, the temperature is controlled at 90°C, the extrudate is cast, cooled and embossed to obtain a film with a thickness of 0.45m.
[0052] Example 9: A film comprising the following raw materials in parts by weight (kg): A film comprising the following raw materials in parts by weight: 100 parts of a polyolefin matrix resin, 6 parts of a crosslinking agent, 2 parts of a silane, 0.1 parts of a silane hydrolysis catalyst, 0.2 parts of a co-crosslinking agent, and 0.1 parts of an anti-aging agent, wherein the polyolefin matrix resin is an ethylene-1-butene copolymer formed by polymerization of ethylene and 1-butene, and has a density of 0.877 g / cm 3The model is LG Chemical LF675 from South Korea, the cross-linking agent is tert-butyl peroxy 2-ethylhexyl carbonate, the auxiliary cross-linking agent is trimethylolpropane trimethacrylate, the antioxidant is benzoic acid (2,2,6,6-tetramethyl-4-hydroxypiperidinyl) ester, the silane is vinyltriethoxysilane, and the silane hydrolysis catalyst is an organic tin catalyst, specifically dibutyltin dilaurate.
[0053] The method for preparing the above-mentioned adhesive film comprises the following steps: According to the above dosage, the polyolefin matrix resin, crosslinking agent, silane, silane hydrolysis catalyst, co-crosslinking agent and anti-aging agent are mixed evenly, the evenly mixed material is added to the melt extrusion casting machine for extrusion, the temperature is controlled at 90°C, the extrudate is cast, cooled and embossed to obtain a film with a thickness of 0.45m.
[0054] Example 10: A film comprising the following raw materials by weight: 100 parts of a polyolefin matrix resin, 4 parts of a crosslinking agent, 1 part of a silane, 0.1 parts of a silane hydrolysis catalyst, 0.2 parts of a co-crosslinking agent, and 0.1 parts of an anti-aging agent, wherein the polyolefin matrix resin is an ethylene-1-octene copolymer having a density of 0.873 g / cm 3 , the melt index (190℃ / 2.16kg) is 1g / 10min, the model is Dow PV8688, the crosslinking agent is tert-butyl peroxy 2-ethylhexyl carbonate, the auxiliary crosslinking agent is trimethylolpropane trimethacrylate, the antioxidant is benzoic acid (2,2,6,6-tetramethyl-4-hydroxypiperidinyl) ester, the silane is vinyl triethoxysilane, and the silane hydrolysis catalyst is an organic tin catalyst, specifically dibutyltin dilaurate.
[0055] The method for preparing the above-mentioned adhesive film comprises the following steps: According to the above dosage, the polyolefin matrix resin, crosslinking agent, silane, silane hydrolysis catalyst, co-crosslinking agent and anti-aging agent are mixed evenly, the evenly mixed material is added to the melt extrusion casting machine for extrusion, the temperature is controlled at 90°C, the extrudate is cast, cooled and embossed to obtain a film with a thickness of 0.45m.
[0056] Comparative Example Comparative Example 1: A film, which differs from Example 1 in that no silane is added.
[0057] Comparative Example 2: A film, which differs from Example 1 in that no silane hydrolysis catalyst is added.
[0058] Comparative Example 3: A film, which is different from Example 1 in that the amount of silane hydrolysis catalyst added is 0.2 parts.
[0059] Comparative Example 4: A photovoltaic cell assembly encapsulation film, comprising a polyolefin film layer, wherein the preparation method thereof specifically comprises the following steps: Step S1, according to the raw material ratio of the polyolefin film layer, 100 parts of POE, 0.2 parts of 2,4-dichlorobenzoyl peroxide (cross-linking agent), 0.2 parts of 3 (ethoxy) trimethylolpropane triacrylate (cross-linking aid), 0.1 parts of cyanuric chloride polymer (UV stabilizer), 0.3 parts of 2-(2-hydroxy-5-methylphenyl) benzotriazole (UV absorber), 0.15 parts of 2,6-di-tert-butyl-4-methylphenol (thermal stabilizer), 0.15 parts of tris(2,4-di-tert-butylphenyl) phosphite (thermal stabilizer), 10 parts of POE grafted organosiloxane (compatibilizer) are weighed respectively, and added into a mixing kettle, stirred and mixed, and the temperature of the mixing kettle is controlled at 30°C to 55°C. When the liquid additive is fully absorbed by the POE particles, the mixing is completed to obtain a first mixture; Step S2, adding the first mixture into the hopper of the casting extruder of the film forming production line, melting, plasticizing and mixing the raw materials at a temperature of 60°C to 100°C through the casting machine, extruding, pulling and embossing through the casting die to obtain a polyolefin film layer with a thickness of 0.7 mm, i.e., a photovoltaic cell module encapsulation film.
[0060] Performance testing Adhesive films were prepared according to the above examples and comparative examples, and the properties of the adhesive films were tested according to the following methods. The test results are recorded in Table 1.
[0061] 1. Dynamic friction coefficient: Cut the prepared film into a size of 80mm×63mm, and use solar ultra-white cloth-textured glass (4mm thick, 200mm×300mm in size) to fit the film. According to GB10006-88 "Determination of friction coefficient of plastic films and sheets", the dynamic friction coefficient between the embossed surface of the film and the embossed surface of the glass is tested at 23±2℃ and 40-60%RH. The film is sealed with PE tape and placed in a 0℃ refrigerator for 24h to test the dynamic friction coefficient between the film and the glass sheet.
[0062] 2. Peel strength with glass: According to GB / T 2790 "Adhesive 180° Peel Strength Test Method", the test is carried out after being placed in normal humidity and 121℃, 100% RH environment for 24 hours. The peeling angle is 180° and the peeling speed is 100mm / min.
[0063] Table 1 Performance test results of the film It can be seen from the data in Table 1 that in Example 1, vinyl triethoxysilane and dibutyl tin dilaurate are used as silane and silane hydrolysis catalyst respectively, tert-butyl peroxy 2-ethylhexyl carbonate is used as a cross-linking agent, and ethylene-1-butene copolymer is used as a polyolefin matrix resin. After mixing, extrusion and casting, the prepared film has a high dynamic friction coefficient and peel strength measured in a humid environment, indicating that in the presence of water molecules, the film can form a good bonding effect with the glass and is not easy to slip.
[0064] In Example 2, vinyl triethoxysilane and dibutyl tin dilaurate are used in a mass ratio of 1:0.001. The adhesive film prepared thereby still has a good dynamic friction coefficient, a high bonding strength with the glass, and is not prone to slippage.
[0065] In Example 3, vinyl triethoxysilane and dibutyltin(dodecylsulfide) were used in a mass ratio of 1:0.01. Compared with Example 1, the dynamic friction coefficient and peel strength were reduced, but the dynamic friction coefficient was still greater than 0.4, and still had a good anti-slip effect.
[0066] In Examples 4 and 5, dibutyltin dilaurate is used as a silane catalyst, and vinyltrimethoxysilane and vinyltriethoxy oligomer are used as silanes, respectively. The adhesive films prepared in Examples 4 and 5 have an anti-slip effect similar to that of Example 1. Compared with Example 1, Example 6 uses vinyltriethoxy oligomer and di(dodecylsulfide)dibutyltin, and the prepared adhesive film has a dynamic friction coefficient similar to that of Example 1. When the adhesive film is bonded to glass in a humid environment, the anti-slip effect of the adhesive film is good.
[0067] Compared with Example 1, Example 7 uses vinyl triethoxysilane and dibutyl tin dithioacetate in a mass ratio of 1:0.01, and the anti-slip effect of the prepared film is similar to that of Example 1.
[0068] Compared with Example 1, Example 8 has a reduced amount of cross-linking agent, an increased amount of silane, and a reduced amount of silane hydrolysis catalyst. Although its dynamic friction coefficient does not change much in a humid environment, the peel strength decreases slowly after being placed in a humid environment, indicating that an increase in the amount of silane can significantly enhance the bonding strength between the film and the glass.
[0069] Compared with Example 1, Example 9 increases the amount of silane hydrolysis catalyst and silane. Although the adhesive film prepared in Example 9 has a higher initial peel strength, the peel strength decreases significantly in a humid environment.
[0070] In Example 10, ethylene-1-octene copolymer is used as the polyolefin base resin, and the adhesive film prepared therefrom has a large dynamic friction coefficient with glass in a humid environment, high bonding strength, and good anti-slip effect.
[0071] Compared with Example 1, Comparative Examples 1 and 2 do not add silane and silane hydrolysis catalyst respectively. The dynamic friction coefficient of the adhesive films prepared in Comparative Examples 1 and 2 is small in a humid environment, and the peel strength between the films and the glass is reduced, and the anti-slip effect is weakened.
[0072] The amount of silane hydrolysis catalyst used in Comparative Example 3 is significantly increased compared with Example 1. As shown in Table 1, the friction coefficient of the film in a humid environment is reduced, the peel strength is weakened, and the anti-slip effect is reduced.
[0073] Comparative Example 4 is a photovoltaic module encapsulation film prepared by the prior art, which contains POE, a cross-linking agent, a co-cross-linking agent, etc., and adds compatibility to improve the compatibility of each component, but the anti-slip effect of the encapsulation film prepared in a humid environment is not significant.
[0074] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A composition for reducing the relative displacement between a film and a glass in a humid environment, characterized in that: The adhesive film comprises silane and a silane hydrolysis catalyst, wherein the silane hydrolysis catalyst promotes the hydrolysis of the silane, thereby the adhesive film is bonded to the glass.
2. The composition for reducing relative displacement between an adhesive film and a glass in a humid environment according to claim 1, characterized in that: The silane hydrolysis catalyst is an organic tin catalyst, the general formula of which is R n S n X4, wherein: n is an integer of 1-4, R is a linear or branched C1-C30 alkyl group, a C5-C14 cycloalkyl group or a C6-C16 aryl group, and X is a substituent selected from one of halogen, hydroxyl, carboxyl, amino, ester, thiol alkyl, anhydride, isocyanate, mercapto, sulfonic acid, epoxy or cyano groups.
3. The composition for reducing relative displacement between adhesive film and glass in a humid environment according to claim 2, characterized in that: The organotin catalyst is selected from one or more of dibutyltin dilaurate, dibutyltin dineodecanoate, dibutyltin dithioacetate, dibutyltin di(dodecylsulfide), dibutyltin dioleate, dibutyltin diacetate, stannous octoate, dialkyltin dimaleate, and alkyltin dithiolate.
4. The composition for reducing relative displacement between an adhesive film and a glass in a humid environment according to claim 1, characterized in that: The silane is selected from one or more of vinyltrimethoxysilane, vinyltriethoxysilane, tetramethyltetravinylcyclotetrasiloxane, aminopropyltriethoxysilane, aminopropyltrimethoxysilane, vinyltriacetoxysilane, isobutyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and vinyltriethoxy oligomer.
5. The composition for reducing relative displacement between adhesive film and glass in a humid environment according to claim 1, 3 or 4, characterized in that: The mass ratio of the silane to the silane hydrolysis catalyst is 1:0.001-0.01, the silane is vinyl triethoxysilane, and the silane hydrolysis catalyst is dibutyl tin dilaurate.
6. The composition for reducing relative displacement between an adhesive film and a glass in a humid environment according to claim 1, 3 or 4, characterized in that: The mass ratio of the silane to the silane hydrolysis catalyst is 1:0.001-0.01, the silane is vinyltrimethoxysilane, and the silane hydrolysis catalyst is didodecylsulfide dibutyltin.
7. A film, characterized in that: The invention comprises a polyolefin matrix resin, a crosslinking agent, an auxiliary crosslinking agent, a silane hydrolysis catalyst and silane, wherein the polyolefin matrix resin contains 0.1-2 parts by weight of silane and 0.001-0.1 parts by weight of the silane hydrolysis catalyst relative to 100 parts by weight of the polyolefin matrix resin, so that the silane hydrolysis catalyst promotes the hydrolysis reaction of the silane, thereby bonding the adhesive film to the glass.
8. The adhesive film according to claim 7, characterized in that: With respect to 100 parts by weight of the polyolefin base resin, 0.5-1 parts by weight of silane and 0.002-0.01 parts by weight of the silane hydrolysis catalyst are contained.
9. The adhesive film according to claim 7, characterized in that: The silane hydrolysis catalyst is an organic tin catalyst, the general formula of which is R n S n X4, wherein: n is an integer of 1-4, R is a linear or branched C1-C30 alkyl group, a C5-C14 cycloalkyl group or a C6-C16 aryl group, and X is a substituent selected from one of halogen, hydroxyl, carboxyl, amino, ester, thiol alkyl, anhydride, isocyanate, mercapto, sulfonic acid, epoxy or cyano groups.
10. The adhesive film according to claim 9, characterized in that: The organotin catalyst is selected from one or more of dibutyltin dilaurate, dibutyltin dineodecanoate, dibutyltin dithioacetate, dibutyltin di(dodecylsulfide), dibutyltin dioleate, dibutyltin diacetate, stannous octoate, dialkyltin dimaleate, and alkyltin dithiolate.
11. The adhesive film according to claim 7, characterized in that: The silane is selected from one or more of vinyltrimethoxysilane, vinyltriethoxysilane, tetramethyltetravinylcyclotetrasiloxane, aminopropyltriethoxysilane, aminopropyltrimethoxysilane, vinyltriacetoxysilane, isobutyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane and vinyltriethoxy oligomer.
12. The adhesive film according to claim 7, characterized in that: The crosslinking agent is selected from one or more of benzoyl peroxide, tert-amyl peroxy 2-ethylhexyl carbonate, di(tert-butyl peroxy) diisopropylbenzene, tert-butyl peroxy benzoate, tert-butyl peroxy 2-ethylhexyl carbonate, n-butyl-4,4-di-tert-butyl peroxyvalerate, 1,1-di-tert-butyl peroxy-3,3,5-trimethylcycloethane and 1,1-di-tert-butyl peroxy-3,3,5-trimethylcycloethane, and triallyl isocyanurate.
13. A method for reducing relative displacement between an adhesive film and glass in a humid environment, characterized in that: The following steps are involved: (a) preparing a film containing silane and a silane hydrolysis catalyst; (b) Laying the adhesive film on the glass; (c) the silane hydrolysis catalyst promotes the hydrolysis of the silane, undergoes a dehydration reaction with the glass, and forms a chemical bond; (d) The adhesive film is bonded to the glass.
14. The method for reducing relative displacement between the adhesive film and the glass in a humid environment according to claim 13, characterized in that: The adhesive film is selected from the adhesive film according to any one of claims 7 to 12.
Citation Information
Cited By
Silane polymer, adhesive film for packaging photovoltaic module and application of adhesive film
CN121405943A